La Academia de Atenas como foco de formación humanística para paganos y cristianos. Los casos de Juliano, Basilio y Gregorio Nacianceno - Blázquez, J.M. (Gerión. Revista de Historia Antigua, 2001)
In the Academy of Athens, in the Fourth Century A.D., coincided Basilius of Cesarea and Gregory of Nazianzus, and possibly Jullian, the future emperor. Philosophy was studied and always was present the dialectic Paganism versus Christianity. The autor are also studied here the intellectual atmosphere and the relationships between professor and students.